A Novel in situ Approach to Studying Pancreatic Ducts in Mice - Gál, Eleonóra; Dolenšek, Jurij; Stožer, Andraž; Pohorec, Viljem; Ébert, Attila; Venglovecz, Viktória (Frontiers in Physiology, 2019)
The tissue slice technique offers several benefits compared to isolated cells and cell clusters that help us understand the (patho)physiology of several organs in situ. The most prominent features are preserved architecture and function, with intact homotypic and heterotypic interactions between cells in slices. In the pancreas, this technique has been utilized successfully to study acinar and endocrine islet cells. However, it has never been used to investigate ductal function. Since pancreatic ductal epithelial cells (PDECs) play an essential role in the physiology of the pancreas, our aim was to use this technique to study PDEC structure and function in situ. 8-16 weeks old C57BL/6 mice were used for preparation of pancreas tissue slices. Low melting point agarose was injected into the common bile duct and the whole organ was extracted. For morphological studies, pieces of tissue were embedded in agarose and cryosectioned to obtain 15 µm thick slices. In order to visualize pancreatic ducts, (i) the Giemsa dye was added to the agarose and visualized using light microscopy or (ii) immunostaining for the cystic fibrosis transmembrane conductance regulator (CFTR) was performed. For functional characterization, agarose-embedded tissue was immediately cut to 140 µm thick tissue slices that were loaded with the cell permeant form of the Oregon Green 488 BAPTA-1 dye and used for confocal calcium imaging. Giemsa staining has shown that the injected agarose reaches the head and body of the pancreas to a greater extent than the tail, without disrupting the tissue architecture. Strong CFTR expression was detected at the apical membranes of PDECs and acinar cells, whereas islet cells were completely negative for CFTR. Stimulation with chenodeoxycholic acid (CDCA, 1mM) resulted in a robust transient increase in intracellular calcium concentration that was readily visible in >40 ductal cells per slice. Our results confirm that the acutely-isolated pancreas tissue slice technique is suitable for structural and functional investigation of PDECs and their relationship with other cell types, such as acini and endocrine cells in situ. In combination with different genetic, pharmacological or dietary approaches it could become a method of choice in the foreseeable future.